Doxing Phenomenon in Indonesia: Amid Waiting for Privacy Settings - Sayid Muhammad Rifqi Noval (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The activity of privacy data dissemination in cyber world today often happens to people who allegedly made mistakes and went viral. Internet users often provide the detailed information through the easy access of various information today, as if it does not violate the law and even expected helping the process of identifying the perpetrator. In Fact, this action is close to what we call as doxing, the privacy violation. The research method of this paper is normative juridical with statute approach, case approach, analytical approach, and comparative approach. The data source of this research is secondary data. The specification of this study is analytical descriptive. The results of this study identified several regulations that could be applied on doxing perpetrators, especially the provisions set out in Law No. 19 of 2016, although the provisions do not specifically address doxing. Several concepts to be considered regarding doxing cases are to file a tort claim regarding privacy information, ie, the tort of public disclosure of private facts, or legal recovery for victims by carrying the concept of the tort of intentional infliction of emotional distress (IIED) claim that applies in some states of the United States.